Aplikasi Pengajuan Job Card pada PT Arutmin Indonesia Tambang Kintap Berbasis Web Mobile - Isabella Yulinshia Citra Valentina (Journal Information Technology Trends (JITRENDS), 2025)
Complaint Work Card is a work card complaint for employees if there is a problem about the workplace, the employee will complain about the problem of using work cards or Working Cards, one of the companies that uses this Work Card, namely PT Arutmin Indonesia Mine Kintap. Job card complaints at PT Arutmin are still using manual complaints. If employees find a problem, they are required to fill out a complaint form in the office and submit it to the admin, then the admin will notify the maintenance team to handle the problem. As a result, with manual complaints requiring employees to come to the office, many employees directly contact the maintenance team without filling out the form. The solution to this problem is the creation of a Mobile Web-Based Work Card Complaint Application at PT Arutmin Indonesia Mine Kintap. The application development model used is the waterfall model, designed using ERD, CDM, PDM, and UML using PHP programming language and MySQL Database. The purpose of the Work Card complaint application is to assist employees in making complaints and facilitate the admin team in managing complaint reports.